Teori Perkembangan Sosial dan Kepribadian dari Erikson (Konsep, Tahap Perkembangan, Kritik & Revisi, dan Penerapan): Erikson’s Theory of Social and Personality Development (Concept, Developmental Stages, Critiques and Revisions, and Applications) - Rizki, Najrul jimatul (Perkumpulan Peneliti dan Pegiat Literasi, 2022)
Erikson's theory of social development and personality provides a framework for understanding the stages of individual development and the psychosocial conflicts encountered. This study adopted a qualitative literature-type approach to analyze the application of Erikson's theory in education, especially in the context of recognizing the stages of student development, identity formation, cooperation, conflict handling, autonomy development, and recognition of diversity. This study examined the academic literature, including relevant journals, books, and other published sources, to explore how the principles of Erikson's theory can be integrated into pedagogical practice. The results of the literature analysis showed that the application of Erikson's theory in an educational context supports the creation of a learning environment conducive to the holistic development of students, facilitates the formation of positive identities, the development of social skills, and an understanding and appreciation of cultural diversity. This research confirmed that an in-depth understanding of students' psychosocial needs at every stage of development by educators was key to maximizing students' learning potential and personal growth, ensuring optimal development of students in educational contexts.